(7-4i)+(7+9i)=

Simple and best practice solution for (7-4i)+(7+9i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7-4i)+(7+9i)= equation:


Simplifying
(7 + -4i) + (7 + 9i) = 0

Remove parenthesis around (7 + -4i)
7 + -4i + (7 + 9i) = 0

Remove parenthesis around (7 + 9i)
7 + -4i + 7 + 9i = 0

Reorder the terms:
7 + 7 + -4i + 9i = 0

Combine like terms: 7 + 7 = 14
14 + -4i + 9i = 0

Combine like terms: -4i + 9i = 5i
14 + 5i = 0

Solving
14 + 5i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 5i = 0 + -14

Combine like terms: 14 + -14 = 0
0 + 5i = 0 + -14
5i = 0 + -14

Combine like terms: 0 + -14 = -14
5i = -14

Divide each side by '5'.
i = -2.8

Simplifying
i = -2.8

See similar equations:

| 2t^2-t-36=0 | | 2ln(2x)=4forx | | g(x)=-4x^2+44x-96 | | x+34+90+x+64=180 | | T^2-t-18=0 | | X=14-5 | | (2y^2)-y-21=0 | | 7.22=6.28r | | 2+2Y-Y^2=0 | | (4/5)^-2 | | 1-3x^3=0 | | (3y-2x)dx-(2y-x)dy=0 | | (4y+3)(2+y)=0 | | 45=1/3a*5 | | (2x-3)(8x+6)=0 | | (4-y)(4y+6)=0 | | 294=12-v | | .6X=1800 | | 55=2x+1y | | 9t^2=4-7t | | (5z-2)(7-z)=0 | | 15x^2+31=-10 | | 28+7(x)=-28 | | 5x^2+5y^2-10x+5y-20=0 | | 9x+5x-6x=54+2 | | 40=7x+x^2 | | d+4.001=5.999 | | 3x^3-6x^2+9X-18=0 | | 2x-105/12 | | 25a-7=-12 | | (V+10)(v-10)= | | 0=2x^3-5x |

Equations solver categories